A time of plenty, a world of need: the role of food aid in 2020 - Webb, Patrick (International Food Policy Research Institute, 1995)
Food aid is one of the constants of human experience. The storage of food as public provision against crises is a practice recorded since Babylonian times. Since the 1950s, the practice has taken on a more international (and often political) character, with food being channeled mainly from industrialized to developing countries. In 1993, global redistribution of food by public-sector agencies reached a record 17 million tons. However, in 1994, total food aid fell. Demand for food aid will not be lower in 2020 than it is today. The supply will depend partly on how effectively food aid is targeted and managed, and partly on the priority given by donors to the problems that are best addressed through food aid: namely, acute and chronic food insecurity. But, if food aid levels are to increase, the world's major donor nations will have to make the alleviation of mass food insecurity, in times of peace as well as in times of crisis, an explicit and urgent priority.